Ortho-allylation of 1-arylpyrazoles with allyl phenyl ether via iron-catalyzed C-H bond activation under mild conditions - Asako, Sobi (2014)
An iron salt and a bipyridine-type ligand catalyze the ortho-allylation of 1-arylpyrazoles and congeners with allyl phenyl ether under mild conditions (0 °C). The ligand, an organozinc base, and the nature of the allylating reagent are crucial for the success of this reaction. Under these conditions, a competitive phenylation reaction is largely retarded, and cross-coupling of the organozinc with the allyl electrophile is minimized. The reaction may proceed via iron-catalyzed ortho C[BOND]H activation to form a metallic intermediate, which then reacts with the allyl ether in a γ selective fashion.